Informal governance and legitimacy in EU politics. Issue 7 (10th November 2018) - Kleine, Mareike
ABSTRACT: Informal governance often holds an aura of the covert and exclusive – aspects that are difficult to square with the ideal of a democratic process. Unfortunately, existing analyses mostly focus on the effect of informal governance on transparency, ignoring other channels through which a political order may generate legitimacy. However, existing analyses quite often conflate different types of informal governance or consider predominantly its effect on transparency and accountability. This article argued that the relationship between informal governance and legitimacy is much more complex and to some extent even counter-intuitive. To see this, I distinguish three channels of legitimation – input, throughput, and output – and discuss how various forms of informal governance affect it. The article has implications for scholarly debates on the legitimacy of global governance, studies of informal governance, and practical implications for the reform of international organizations.